2021
DOI: 10.1063/5.0063258
|View full text |Cite
|
Sign up to set email alerts
|

Action spectroscopy of the isolated red Kaede fluorescent protein chromophore

Abstract: The incorporation of fluorescent proteins into biochemical systems has revolutionized the field of bioimaging. In a bottom-up approach, understanding the photophysics of fluorescent proteins requires detailed investigations on the light-absorbing chromophore, which can be achieved by studying the chromophore in isolation. This paper reports a photodissociation action spectroscopy study on the deprotonated anion of the red Kaede fluorescent protein chomophore, demonstrating that at least three isomers -assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…These sub-populations can be associated with different conformers or tautomers, 45,48,50,[158][159][160] diastereomers, 44,46,47,139 or with post-DMS fragmentation of an aggregate species (e.g., solvent clusters, proton-bound analyte dimers). 49,161 Although the identity of each feature can be determined by, for example, collision-induced dissociation, 48 hydrogen-deuterium exchange, 162,163 and/or trapped ion spectroscopy, 18,[164][165][166][167][168][169] there is no simple a priori method to determine whether a particular analyte will exhibit multiple features in a DMS ionogram. This complicates the use of DMS in an analytical setting -if an analyte exhibits multiple populations that vary with DMS conditions, but the device is set to select only one sub-population, one runs the risk of underestimating analyte concentration in quantification experiments.…”
Section: What Else Can We Learn From Dms?mentioning
confidence: 99%
See 1 more Smart Citation
“…These sub-populations can be associated with different conformers or tautomers, 45,48,50,[158][159][160] diastereomers, 44,46,47,139 or with post-DMS fragmentation of an aggregate species (e.g., solvent clusters, proton-bound analyte dimers). 49,161 Although the identity of each feature can be determined by, for example, collision-induced dissociation, 48 hydrogen-deuterium exchange, 162,163 and/or trapped ion spectroscopy, 18,[164][165][166][167][168][169] there is no simple a priori method to determine whether a particular analyte will exhibit multiple features in a DMS ionogram. This complicates the use of DMS in an analytical setting -if an analyte exhibits multiple populations that vary with DMS conditions, but the device is set to select only one sub-population, one runs the risk of underestimating analyte concentration in quantification experiments.…”
Section: What Else Can We Learn From Dms?mentioning
confidence: 99%
“…[11][12][13][14][15] For example, in cases where the gasphase and solution-phase analyte structures differ, the degree of microsolvation can dictate whether the gas-phase or solutionphase favoured isomer will be present in the experimental ensemble. [16][17][18] The number of solvent ligands required to transition between the preferred gas-and solution-phase isomers depend on the analyte. In fact, there is no ''back-of-theenvelope'' method that can estimate this quantity, or the number of solvent ligands required to observe the onset of different condensed-phase properties (e.g., electronic or vibrational spectra, [19][20][21][22][23][24] molecular conformation, [25][26][27] chemical reactivity 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…For these two chromophores, there is a concomitant increase in the calculated vertical detachment energy (VDE, Table ). It is worth noting that gas-phase rKFP – was recently investigated by some of the present authors using isomer-specific photodissociation action spectroscopy, where it was shown that three gas-phase forms may be generated using electrospray ionization (two deprotomers and one tautomer). Following on from that study, judicious choice of solvent and electrospray conditions in the present work allowed generation of a pure gas-phase ensemble of the phenoxide deprotomer shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 88%
“… a Values in parentheses are solvation-induced spectral shifts, i.e., relative to the bare anion. b Reference . c Reference . …”
Section: Results and Discussionmentioning
confidence: 99%
“…Other examples of experiments that combine ion mobility with PD action spectroscopy are FAIMS separation with cryogenic UV/vis PD spectroscopy of peptides from Rizzo's group, 180,199,200 FAIMS separation with room temperature UV/ vis PD spectroscopy from the Hopkins group, 96,[201][202][203][204] drift mobility separation with cryogenic spectroscopy from Bieske's group, 158,159 and drift mobility separation with room temperature photodissociation and photoisomerization from Bieske's group 72,[205][206][207][208][209][210][211][212][213][214][215][216][217][218] and Dugourd's group. 219,220 Tandem IMS and photoactivation Tandem IMS has been combined with photoactivation to observe photoisomerism.…”
Section: Ion Mobility Spectrometry With Photodissociationmentioning
confidence: 99%